Nephrotic Syndrome as a Complication of Systemic Calcitonin Amyloidosis From Long-Standing Metastatic Medullary Thyroid Cancer - Samantha M. Siskind, MD; Sakshi Yadav, MBBS; Melinda Solomon, MD; Philip E. Knapp, MD, MS; Hanni Menn-Josephy, MD; Jean Francis, MD; Helmut G. Rennke, MD; Rivka Ayalon, MD; Katherine L. Modzelewski, MD (AACE Clinical Case Reports, 2024)
Background/Objective: Medullary thyroid cancer often results in elevated calcitonin levels, which can cause localized formation of calcitonin amyloid, though rarely complications of systemic calcitonin amyloidosis have been reported. The objective of this report is to encourage awareness of calcitonin amyloid causing nephrotic syndrome in patients with metastatic medullary thyroid cancer. Case Report: A 65-year-old woman with weakness, fatigue, anasarca, anemia, thrombocytopenia, venous and arterial thrombi, and a cavitary right lung lesion was transferred for care. She had a 14-year history of metastatic medullary thyroid cancer, status post-thyroidectomy and tyrosine kinase inhibitor therapy, adrenocorticotropic hormone-dependent Cushing syndrome in remission, and recently diagnosed nephrotic syndrome. On admission, she had lower extremity edema and scattered ecchymoses. Labs showed creatinine 0.62 mg/dL (0.7-1.3 mg/dL), morning cortisol >119.6 ug/dL (4-23 ug/dL), adrenocorticotropic hormone 426 pg/mL (6-50 pg/mL), 24-hour urine cortisol 6115.2 mcg/24 h (4-50 mcg/24 h), calcitonin 39 373 pg/mL (≤5 pg/mL), and carcinoembryonic antigen level 484.8 ng/mL (0-4.9 ng/mL). Kidney biopsy showed amyloidosis, which stained positive for calcitonin. Discussion: Systemic calcitonin amyloidosis is not well-documented in medullary thyroid cancer. To our knowledge, there are 2 previous case reports describing nephrotic syndrome secondary to calcitonin amyloid in the setting of medullary thyroid cancer. Conclusion: This case supports a small body of evidence that metastatic medullary thyroid cancer can result in systemic calcitonin amyloidosis and its complications, including nephrotic syndrome. Clinicians should consider nephrotic syndrome as a potential complication in patients with metastatic medullary thyroid cancer, particularly in those with long-standing calcitonin elevation and characteristic symptoms.